Development of New Synthetic Pathways for Renewable Energy Storage - Iqbal, Ayesha; Abbas, Waheed; Ghouri, Mohsin Saleem; Rasheed, Fatima; Hameed, Muhammad Zahid; SThorai; Naheed, Sahrish; Zuha Malik; Aroosa Arif; Abdullah, Obaid Muhammad (Indus Journal of Bioscience Research, 2025)
Due to the intermittent nature of renewable energy sources (solar, wind), there is a need to develop efficient, scalable, and sustainable energy storage systems. Existing energy storage technologies face fundamental challenges, and this study aimed to tackle those challenges by exploring new synthetic routes for novel materials. It focused on enhancing the performance, scalability, and environmental sustainability of energy storage technologies, including lithium-ion batteries, supercapacitors, and hydrogen storage systems. Designing metal-organic frameworks (MOFs), perovskites and polymer electrolytes via green chemistry principles to minimize the environmental impact of produced materials. The cyclic voltammetric, electrochemical impedance spectroscopic and long-term cycle stability measurements of electrochemical performance were conducted. Density Functional Theory (DFT) simulations for computational modelling were used to predict material properties and optimize reaction pathways. In these results, MOF based Lithium-ion batteries achieved the best energy density (310 Wh/kg); polymer based supercapacitors exhibited high power density (2000 W/kg) and cycling stability (94% retention after 1000 cycles). Recently stability of perovskite-based hydrogen storage systems was improved to 88% of the capacity after 1000 cycles. The results confirmed that using high-performance materials from 21st century fibres with sustainable synthesis approaches solved key performance and sustainability challenges. It lays a foundation towards stackable and sustainable energy storage systems, which can be used in technological energy grids, electric vehicles, and portable devices.